Educational Socialization of Dangerous to Aircraft Activities in the Aviation Operations Safety Area - Yuniar, Dwi Candra; Oka, I Gusti Agung Ayu Mas; Putra, Bambang Wijaya; Febiyanti, Herlina; Munir, M Syahrul; Pratama, M Aldyan Putra; Alhafidz, Rafirli Yuspa; Alaudin, Afif (Graduate Program Magister Manajemen Pendidikan, 2022)
Implementing socialization within the context of the Tridharma of Higher Education, including conducting research and compiling Scientific Journals at the Palembang Aviation Polytechnic in South Sumatra. Furthermore, the goal of this effort is to improve broad public understanding and awareness of Depati Amir-Bangka Airport. This action also informs the safe distance and any behaviors that may harm aviation operations, particularly in the Aviation Operations Safety Area, as well as individuals who reside nearby. Socialization is accomplished by exposure by resource individuals and dialogues with people who reside near Depati Amir Bangka Airport. So that participants are aware of the outcomes of socialization associated to actions that may risk flights.The socializing findings were then publicized on the Palembang Aviation Polytechnicsocial media and the JMKSP Journal.